2021
DOI: 10.1044/2021_lshss-21-00016
|View full text |Cite
|
Sign up to set email alerts
|

“Two Friends Spending Time Together”: The Impact of Video Visual Scene Displays on Peer Social Interaction for Adolescents With Autism Spectrum Disorder

Abstract: Purpose Social interaction poses many challenges for adolescents with autism spectrum disorder (ASD) and complex communication needs. The purpose of this study was to investigate the impact of video visual scene displays (video VSDs) on communication during interactions between adolescents with ASD and peer partners. Method This study used an across-participant multiple-baseline single-case experimental design. Four adolescents with ASD and complex comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Current studies show examples of how apps for communication can increase social participation for young people with intellectual disabilities (e.g. Babb et al, 2021 ; Caron, 2018 ) and giving supporting staff access to knowledge about new innovations is therefore essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies show examples of how apps for communication can increase social participation for young people with intellectual disabilities (e.g. Babb et al, 2021 ; Caron, 2018 ) and giving supporting staff access to knowledge about new innovations is therefore essential.…”
Section: Discussionmentioning
confidence: 99%
“… Murphy & Cameron 2008 ; Stans et al, 2019 ; Stewart et al, 2018 ). In this area, development is progressing rapidly and new digital tools are being tested, such as apps that support communication, thus facilitating participation for young people with complex communication difficulties ( Babb et al, 2021 ; Caron, 2018 ). Such assistive technology can also facilitate everyday activities and can lead to less reliance on parents or professionals ( Buchholz et al, 2018 ; Stephenson & Limbrick, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research provides initial evidence that video VSDs may assist individuals with complex communication needs during a variety of communication contexts. For example, Babb, McNaughton, Light, and Caron (2020) reported that a video VSD intervention increased communication between adolescents with autism spectrum disorder (ASD) and their peers with typical development during social interactions. Video VSDs also can be used to provide participation and communication supports during a wide range of community activities, including interactions with unfamiliar communication partners.…”
Section: Video Visual Scene Displaymentioning
confidence: 99%
“…Increases were observed for both completion of community-based activities (e.g., working in a printshop, riding public transportation) and communication (e.g., greeting office staff). In a study with four adolescents with developmental delays, Babb, McNaughton, Light, Caron, et al (2020) described how the use of video VSD supports resulted in increases in communication and participation for all four participants as they worked as volunteers at a food bank.…”
Section: Video Visual Scene Displaymentioning
confidence: 99%
See 1 more Smart Citation